2021
DOI: 10.4132/jptm.2021.07.25
|View full text |Cite
|
Sign up to set email alerts
|

Upward trend in follicular lymphoma among the Korean population: 10-year experience at a large tertiary institution

Abstract: Background: Follicular lymphoma (FL) is the second most common non-Hodgkin lymphoma (NHL) in Western countries. However, it is relatively rare in Asia. This study examined epidemiologic characteristics of FL in South Korea, with an emphasis on recent trends of increase in cases. Methods: We retrospectively examined 239 cases of newly diagnosed FL at a large tertiary institution in Korea (Asan Medical Center, Seoul, Republic of Korea) between 2008 and 2017. Age-adjusted incidence rates and clinicopathological v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…For example, the age‐matched population‐based incidence of FL in Japan is high but remains significantly lower than that of western countries, 11 possibly due to the lower incidence of erroneous IGH translocation resulting in t(14;18). A similar trend has been reported in the Korean population 12 . Supporting this difference in FL incidences between Japan and western countries, an earlier study reported that the prevalence of t(14;18)‐positive FL cells in Japanese individuals is lower than that in Germans 13 .…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…For example, the age‐matched population‐based incidence of FL in Japan is high but remains significantly lower than that of western countries, 11 possibly due to the lower incidence of erroneous IGH translocation resulting in t(14;18). A similar trend has been reported in the Korean population 12 . Supporting this difference in FL incidences between Japan and western countries, an earlier study reported that the prevalence of t(14;18)‐positive FL cells in Japanese individuals is lower than that in Germans 13 .…”
Section: Introductionsupporting
confidence: 80%
“…A similar trend has been reported in the Korean population. 12 Supporting this difference in FL incidences between Japan and western countries, an earlier study reported that the prevalence of t(14;18)-positive FL cells in Japanese individuals is lower than that in Germans. 13 However, the incidence of isolated pure ISFN has not been investigated in the Japanese population.…”
Section: Introductionmentioning
confidence: 89%
“…The literature has listed possible risk factors for follicular lymphoma (FL): a family history of NHL (1.99-fold increased risk of FL), hepatitis C virus (a 2.73-fold increased risk of FL), select autoimmune diseases, allergy/atopy, and alcohol consumption [ 8 , 9 ]. The incidence of FL has shown a rising trend in some areas, such as Canada, Poland, Japan, South Korea, and Taiwan; however, the reasons for this remain unknown [ 2 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have investigated the incidence of FL in Asia owing to its relative rarity in Asia compared with western countries [ 7 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In Singapore, the time trend in the incidence of NHL among men and women increased in 1998–2012, but the incidence of FL did not significantly increase [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation